MILITARY STATUS AND STUDENT MOTIVATION: INGREDIENTS OF SUCCESSFUL EDUCATION - Юрків, Оксана (SWorldJournal, 2024)
Professional training of the future doctor is a long process of his formation not only as a specialist, but also as a person with a personal focus on the personal and professional self-improvement throughout life. In the conditions of a market economy, w